School-Based Management (SBM) Practices in Malaysia: A Systematic Literature Review - Isa, Anniliza Mohd; Mydin, Al-Amin; Abdullah, Abdul Ghani Kanesan (Human Resource Management Academic Research Society, 2020)
School-Based Management (SBM) has been practised in Malaysia over the past two decades. However, SBM studies still found little attention among social science researchers in Malaysia. The details in the success of SBM implementation are still unclear. Thus, the researcher has emphasized the need to conduct a systematic review of existing studies to collect information on SBM in Malaysia. Four questions have been established in this review which are; (1) How SBM is implemented in Malaysia? (2) What is the classification level of SBM implementation strength in Malaysia? (3) To what extent are principals, teachers, parents and communities involved in SBM in Malaysia? and lastly, (4) What are the issues and challenges faced in schools related to SBM? The results of a decade-long literature review on SBM in Malaysia showed that SBM implementation in Malaysia was at a moderate level and had used a combination of two models, administrative-control SBM and professional-control SBM. Two critical issues identified from this review were on the role of the school leader and teacher competency. The researcher proposed the need for a standard instrument to evaluate SBM, highlighting the roles of district and state education officers in promoting empowerment among school leaders and teachers, as well as the involvement of the Parent-Teachers Association (PTA). Empowerment among school leaders encompasses leadership capacity while empowerment among teachers includes increasing motivation and professional guidance in various aspects such as pedagogy, professional development, accountability, and integrity